Força crítica em nado atado para avaliação da capacidade aeróbia e predição de performances em nado livre - Papoti, Marcelo [UNESP]; Vitório, Ricardo [UNESP]; Araújo, Gustavo Gomes [UNESP]; Martins, Luiz Eduardo Barreto; Cunha, Sérgio Augusto; Gobatto, Claudio Alexandre [UNESP] (Universidade Federal de Santa Catarina, 2010)
O presente estudo investigou as relações da força crítica (Fcrit) com o limiar de lactato (LL NA) e a intensidade de exercício correspondente ao VO2max (iVO2max) em nado atado (NA) e suas correlações com as performances de 400m (V400) e teste de 30 minutos (VT30) em nado livre (NL). Sete nadadores foram submetidos a teste incremental em NA para determinação do LL NA e da iVO2max. Para determinação da Fcrit, os nadadores realizaram 4 esforços até a exaustão com intensidades (F) correspondente a 87%, 104%, 118% e 134% da iVO2max para obtenção dos tempos limites (tlim). A Fcrit correspondeu ao coeficiente linear da relação entre a F e 1/tlim. Os valores de Fcrit (51,97 ± 4,02 N) foram significativamente diferentes da iVO2max (60,21 ± 8,73 N), mas não do LL NA (45,89 ± 8,73). A Fcrit foi significativamente correlacionada com o iVO2max (0,97), LL NA (0,88), V400 (0,85) e VT30 (0,86). Os resultados sugerem que a Fcrit pode ser utilizada na determinação da capacidade aeróbia, prescrição do treinamento em NA e na predição de performance em NL.

The present study investigated the relationship of critical force (Fcrit) with lactate threshold (LL NA) and the intensity corresponding to VO2max (iVO2max) in tethered swimming (TS), and their correlation with maximal performance in 400-m (V400) and 30-min (VT30) freestyle swimming (FS). Seven swimmers were submitted to a TS incremental test for the determination of LL NA and iVO2max. For the determination of Fcrit, the swimmers performed four exercises to exhaustion at intensities (F) corresponding to 87%, 104%, 118% and 134% of iVO2max for the calculation of time limits (Tlim). Fcrit corresponded to the linear coefficient of the ratio between F and 1/tlim. The maximal performance in FS corresponded to the mean velocity obtained during maximal exercise of 400-m and 30-min crawl swimming. Fcrit (51.97 ± 4.02 N) was significantly lower than iVO2max (60.21 ± 8.73 N) but not than LL NA (45.89 ± 8.73). Fcrit was significantly correlated with iVO2max (0.97), LL NA (0.88), V400 (0.85), and VT30 (0.86). These data suggest that Fcrit can be used for the determination of aerobic capacity, prescription of a TS training program, and prediction of performance in FS.
Critical force during tethered swimming for the evaluation of aerobic capacity and prediction of performances in freestyle swimming
Keywords: Nado atado; Força crítica; Limiar de lactato; Performance; Tethered swimming; Critical force; Lactate threshold; Performance